Implementasi Pembelajaran Mendalam pada Mata Pelajaran IPAS Materi Mitigasi Bencana di SMK Pelayaran Tayu untuk Meningkatkan Kompetensi Kesiapsiagaan Bencana Pelayaran - Nigita Ariyani; Dewi Amaliya (PPPM Polimarin, 2025)
This study aims to examine the implementation of deep learning in IPAS instruction on disaster mitigation to enhance maritime disaster preparedness among students at SMK Pelayaran Tayu. Disaster mitigation is a critical competence in maritime vocational education due to its direct relevance to navigation safety and marine environmental protection. However, IPAS learning is often delivered in a theoretical and fragmented manner, limiting students’ preparedness in real maritime emergency situations. This study employed a mixed-methods approach with a quasi-experimental design involving maritime vocational students. Data were collected through conceptual understanding tests, disaster preparedness questionnaires, classroom observations, and interviews. The deep learning approach was implemented through contextual problem-based activities using real maritime disaster scenarios, such as extreme weather, ship fires, and navigation hazards. The results indicate a significant improvement in students’ maritime disaster preparedness competence, including knowledge, attitudes, and decision-making skills related to disaster mitigation. Qualitative findings further reveal increased student engagement and contextual understanding of maritime risks. This study contributes to the development of IPAS maritime learning by demonstrating that deep learning-oriented instruction can effectively strengthen disaster preparedness in maritime vocational education